Complicated Inguinocrural Hernias: Laparoscopic Vs. Open Surgery in the Emergency Setting - Lucía Aragone; Nicolás Rosasco; Juana Gutierrez; Raul Croceri; Pablo Medina; Daniel Pirchi (Journal of Abdominal Wall Surgery)
IntroductionThe feasibility of laparoscopic treatment for inguinocrural-hernias (ICH) and its advantages over open techniques have already been demonstrated. Nonetheless, there is still no sufficient literature regarding laparoscopy for incarcerated or strangulated ICH in the emergency setting. Our primary outcome was to evaluate the feasibility and safety of laparoscopic surgery (LS) for complicated ICH by comparing outcomes to open surgery (OS).MethodsA comparative retrospective study with prospective case registry was conducted. All patients who underwent ICH repair due to complicated hernias from January 2003 to December 2023 were analyzed and divided into groups according to the approach during surgery: OS (by Lichtenstein technique) or LS (by transabdominal preperitoneal approach). Demographic variables, hernia size and type, surgical time, length of stay, recurrence and other morbidities were compared between groups.ResultsA total of 8282 ICH were operated in the studied period, out of which 162 were included in the study due to incarceration or strangulation. Of these, 83 were treated by OS, while 79 underwent LS. LS showed a reduction in surgical time (70 min IQR60-103 vs. 117 min IQR100-120; p 0.03), length of stay (1.9 days ± 1.4 vs. 2.9 days ± 3.1; p 0.01) and total morbidities (6.3% vs, 16.8%; p 0.04), with a similar recurrence rate (1.2% vs. 1.2%; p1) when compared to OS group.ConclusionLaparoscopic surgery for the treatment of complicated inguinocrural-hernias is a feasible and safe approach. It allows the benefits of minimally invasive surgery, including shorter surgical time, shorter length of stay and fewer postoperative morbidities, without increasing recurrence rate compared to open surgery.